The Influence of Education and Participation in Decision Making on Women's Empowerment - Yahya, Siskawaty; Darman, Darman; Hadjatu, Sri (Eastasouth Institute, 2024)
This research tries to explain the influence of education and partici-pation in decision-making on women's empowerment, by observing a sample of 53 women in the village. The data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) methods using the SMARTPLS version 3 software. The samples were chosen and gathered via purposive sampling and disseminated us-ing an online questionnaire using Google form. The results show that education has an insignificant effect, with a Tstatistics value of 5.600 and P values of 0.000, while participation in decision-making has a significant effect, with a Tstatistics value of 2.295 and P value of 0.022 on women's empowerment.